NarrativePlay: An Automated System for Crafting Visual Worlds in Novels for Role-Playing - Zhao, Runcong; Zhang, Wenjia; Li, Jiazheng; Zhu, Lixing; Li, Yanran; He, Yulan; Gui, Lin (Proceedings of the AAAI Conference on Artificial Intelligence, 2024)
In this demo, we present NarrativePlay -- an innovative system enabling users to role-play a fictional character and interact with dynamically generated narrative environments. Unlike existing predefined sandbox approaches, NarrativePlay centres around the main storyline events extracted from the narrative, allowing users to experience the story from the perspective of a character they chose. To design versatile AI agents for diverse scenarios, we employ a framework built on a Large Language Models (LLMs) to extract detailed character traits from text. We also incorporate automatically generated visual displays of narrative settings, character portraits, and character speech, greatly enhancing the overall user experience.